2005
DOI: 10.1086/431642
|View full text |Cite
|
Sign up to set email alerts
|

Hα‐derived Star Formation Rates for Threez≃0.75 EDisCS Galaxy Clusters

Abstract: We present Hα-derived star-formation rates (SFRs) for three z ≃ 0.75 galaxy clusters. Our 1σ flux limit corresponds to a star-formation rate of 0.10-0.24 h −2 100 M ⊙ yr −1 , and our minimum reliable Hα + [N II] rest-frame equivalent width is 10Å. We show that Hα narrowband imaging is an efficient method for measuring star formation in distant clusters. In two out of three clusters, we find that the fraction of star-forming galaxies increases with projected distance from the cluster center. We also find that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
188
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(209 citation statements)
references
References 55 publications
19
188
2
Order By: Relevance
“…as in Finn et al (2005). In practice, the redshift distributions of high-z and the mid-z samples partly overlap as can be seen from Table 1.…”
Section: Sample Selection and Vlt/fors2 Optical Imagingmentioning
confidence: 72%
See 1 more Smart Citation
“…as in Finn et al (2005). In practice, the redshift distributions of high-z and the mid-z samples partly overlap as can be seen from Table 1.…”
Section: Sample Selection and Vlt/fors2 Optical Imagingmentioning
confidence: 72%
“…X-ray observations with the XMM-Newton satellite of three EDisCS clusters have been published in Johnson et al (2006) with more clusters being observed. H-alpha observations of three clusters have been published in Finn et al (2005) with more clusters also being observed. Finally, the analysis of Spitzer/IRAC observations of all EDisCS clusters is in progress (Finn et al, in preparation).…”
Section: Introductionmentioning
confidence: 99%
“…The grey histogram shows the distribution of all galaxies; the red, green, and blue histograms are those objects belonging to the red sequence, the green valley, and the blue cloud, respectively. dictated by the possibility that the identification of virial entities here using analytic prescriptions, such as the one proposed by Finn et al (2005), might be not appropriate given the unrelaxed nature of these substructures. The resulting distribution of galaxies belonging to the different substructures in the velocity space is shown in Fig.…”
Section: Identification Of the Substructures In The Velocity Spacementioning
confidence: 99%
“…Using the redshift dependence of the critical density and the virial mass to relate the line-of-sight velocity dispersion to the cluster mass, R 200 can be expressed as (see Finn et al 2005)…”
Section: Velocity Dispersionmentioning
confidence: 99%